We are the Salmon Family: Inviting Reciprocal and Respectful Pedagogical Encounters with the Land - Hill, Cher; Whintors, Neva; Bailey, Rick (Engaged Scholar Journal, 2022)
Through this action research project, we endeavour to reconfigure pedagogical encounters involving children and the natural world to be more reciprocal and respectful, as well as responsive to the ecological crisis. The goal of our research is to advance understandings of how to educate children to become good relatives to all the beings on these Lands. We are guided by the question: How can we educate children to live like Salmon People (those Indigenous to this place), which is the sacred responsibility of all those residing on the Coast Salish territories? Practices that contributed to shifting relationship between people and the Land and moved our community beyond our human-centric engagement were participatory and embodied. They included acts to care for Salmon and other beings as relatives, as well as experiencing Land as agential and existing independently of human desire. We see our research as a site for what Kari Grain calls “critical hope.”